2023
DOI: 10.1182/bloodadvances.2022007528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mesenchymal stromal cell–derived vesicular cargo on B-cell acute lymphoblastic leukemia progression

Abstract: Leukemia cells reciprocally interact with their surrounding bone marrow microenvironment (BMM), rendering it hospitable to leukemia cell survival, for instance by release of small extracellular vesicles (sEV). In converse, we show here, that BMM-deficiency of pleckstrin homology domain family M member 1 (PLEKHM1), which serves as a hub between fusion and secretion of intracellular vesicles and is important for vesicular secretion in osteoclasts, accelerates murine BCR-ABL1+ B-cell acute lymphoblastic leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Increasing evidence has demonstrated a bidirectional EV-mediated crosstalk between leukemic cells and many other cell types residing within the BM niche. On the one hand, EVs released by leukemic cells have been described to induce angiogenesis 15,18 , inhibit healthy hematopoiesis 19 , modulate immune cells 20,21 and promote BM niche remodeling, for example by inducing lipolysis, to obtain growth advantage 18,22,23 . On the other hand, it has been found that the microenvironment can support the growth, survival and chemoresistance of leukemic cells through vesiculation 14,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated a bidirectional EV-mediated crosstalk between leukemic cells and many other cell types residing within the BM niche. On the one hand, EVs released by leukemic cells have been described to induce angiogenesis 15,18 , inhibit healthy hematopoiesis 19 , modulate immune cells 20,21 and promote BM niche remodeling, for example by inducing lipolysis, to obtain growth advantage 18,22,23 . On the other hand, it has been found that the microenvironment can support the growth, survival and chemoresistance of leukemic cells through vesiculation 14,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Pleckstrin homology domain family M member 1 (PLEKHM1) deficiency in the bone marrow microenvironment accelerated BCR-ABL + B-ALL disease progression by altering MSC EV cargo ( 98 ). TNF-α secretion by B-ALL cells cause PLEKHM1 deficiency in MSCs that release sEVs increasing the number and improving the function of leukemia initiating cells through the transfer of enriched synthenin and syndecan-1 ( 98 ). As a result of this transfer, phosphorylation of AKT and focal adhesion kinase occurs, which in turn promotes differentiation, migration, and disease progression in BCR-ABL + B- ALL ( 98 ).…”
Section: Lymphoid Neoplasmsmentioning
confidence: 99%
“…TNF-α secretion by B-ALL cells cause PLEKHM1 deficiency in MSCs that release sEVs increasing the number and improving the function of leukemia initiating cells through the transfer of enriched synthenin and syndecan-1 ( 98 ). As a result of this transfer, phosphorylation of AKT and focal adhesion kinase occurs, which in turn promotes differentiation, migration, and disease progression in BCR-ABL + B- ALL ( 98 ). The osteogenic differentiation of BM-MSCs is inhibited by miR-34a-5p carried by sEVs released by T-ALL blasts.…”
Section: Lymphoid Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations